Deleuze and music - Buchanan, Ian, 1969-; Swiboda, Marcel (Edinburgh University Press, 2004)
Drawing out the 'unwritten' book on music from which Deleuze left many clues, but no manuscript, the essays in this volume explore what he said and thought about music and how music informed his thinking.